Analysis of differential metabolites and metabolic pathways in adipose tissue of tree shrews (Tupaia belangeri) under gradient cooling acclimation. (February 2023) - Hou, Dongmin; Chen, Huibao; Jia, Ting; Zhang, Lin; Gao, Wenrong; Chen, Simeng; Zhu, Wanlong
Abstract: In order to investigate the influence of gradient cooling acclimation on body mass regulation in tree shrews ( Tupaia belangeri ), white adipose tissue (WAT) and brown adipose tissue (BAT) in T. belangeri between the control group and gradient cooling acclimation group on day 56 were collected, body mass, food intake, thermogenic capacity, differential metabolites, and related metabolic pathways in WAT and BAT were measured, the changes of differential metabolites were analyzed by non-targeted metabolomics method based on liquid chromatography-mass spectrometry. The results shown that gradient cooling acclimation significantly increased body mass, food intake, resting metabolic rate (RMR), non-shivering thermogenesis (NST), and masses of WAT and BAT. 23 significant differential metabolites in WAT between the gradient cooling acclimation group and the control group, of which the relative contents of 13 differential metabolites were up-regulated and 10 differential metabolites were down-regulated. 27 significant differential metabolites in BAT, of which 18 differential metabolites decreased and 9 differential metabolites increased. 15 differential metabolic pathways in WAT, 8 differential metabolic pathways in BAT, and 4 differential metabolic pathways involved in both WAT and BAT, including Purine metabolism, Pyrimidine metabolism, Glycerol phosphate metabolism, Arginine and proline metabolism, respectively. All of the above results suggested that T. belangeri could use different metabolites of adipose tissue to withstand low temperature environments and enhance their survival. Highlights: Physiological indexes were increased significantly under gradient cooling acclimation. Variation of differential metabolites in WAT and BAT in Tupaia belangeri . Variation of metabolic pathways in WAT and BAT in Tupaia belangeri .